ART Nürnberg 6 : Forum für aktuelle Kunst - Art Network - Tendenz - Performance - Kommunikation. - ART Nürnberg 6, 1991 (Nürnberg : ART Nürnberg Verlag, 1991)
Mehling, Armin ; Winter, Konrad ; Rackel, Sigurd ; Duck, Wolfgang ; Billmayer, Franz ; Green, Marilyn ; Hein, Hannes ; Bolz, Matthias ; Beckmann, Ulrike ; Dumitru, Cristian ; etc.
ART Nürnberg 6 : Forum für aktuelle Kunst - Art Network - Tendenz - Performance - Kommunikation, Nürnberg, 20. - 23. Juni 1991
boek